Medical student perceptions of research and research-orientated careers: An international questionnaire study. (2nd October 2016) - Funston, Garth; Piper, Rory J.; Connell, Claire; Foden, Philip; Young, Adam M. H.; O'Neill, Paul
Abstract: Background: Engaging and inspiring the next generation of physician-scientists at an early stage is recognised as key to ensure the future of medical research. However, little is known about medical student perceptions of research. Objectives: We attempted to ascertain perceptions of research and research-orientated careers from medical students studying in different countries. Methods: An online questionnaire was developed, piloted, and promoted to medical students in various countries. Results: 1625 responses were collected from 38 countries. Analysis was restricted to data collected from countries with >100 responses ( n = 890). Less than half the respondents felt their medical school provided adequate research training. Key perceived barriers to research participation as a student included lack of time and difficulty finding mentors or projects. A significant gender disparity existed in research ambitions of students with females desiring less research involvement. The importance of barriers and satisfaction with research training differed significantly between countries. Conclusions: Students perceive a number of key barriers to research involvement and pursuit of research-orientated careers. Programmes designed to engage students with research should focus on overcoming identified barriers. Greater effort is needed to engage female students who report more significant barriers and less desire to follow research-orientated careers.